Soluciones de la ecuación de Bring-Jerrard - Chávez Cáliz, Ana Cristina (Universidad Michoacana de San Nicolás de Hidalgo. Universidad Nacional Autónoma de México, 2016)
The most popular proof about fifth degree equation not soluble by radicals was given by Evariste Galois, and uses one of the most significant theories for the algebra. In this thesis, we want to give geometric arguments to convince why fifth degree equations cannot be solved by radicals. This aspect is well known since 1888, with Klein's book Lectures on the ikosahedron, and the solution of equations of the fifth degree. The main reference for this thesis is the work of Green On the analytic solution of the equation of fifth degree. Solving equations of degree at most three (which are soluble by radicals), finding the solutions of any equation of fifth degree equates to find the solutions of an equation of the form z5 + az + b = 0; this family of equations is known under the name of Bring-Jerrard equations. Given this fact, it is then desirable to study the solutions of the Bring-Jerrard equations. In this thesis, we see that the complex curve of solutions has a natural Riemann surface structure of genus 4. It is a remarkable fact that the solutions curve prove to be one of the Kepler-Poison polyhedron (the great dodecahedron). Using the structure of Riemann surface of the solutions curve, we can see that address the solution of an equation of fifth degree equivalent to finding an uniformization of the complex curve of genus 4. Uniformization theorem ensures the existence of the function, but the theorem does not say how to obtain it. The story is different for equations of degree 3 and 4, since in these cases, the complex curve of solutions is simply the Riemann sphere, so it is not necessary to appeal to the Uniformization theorem.

La demostración más popular de que las ecuaciones de grado cinco no son solubles por radicales fue dada por Evariste Galois, y usa una de las teorías más significativas para el álgebra: la teoría de Galois. En la presente tesina, deseamos dar argumentos geométricos para convencer por qué las ecuaciones de grado cinco no pueden solucionarse mediante una fórmula con radicales. Este aspecto es bien conocido desde 1888, con el libro de Klein Lectures on the ikosahedron, and the solution of equations of the fifth degree. La principal referencia para esta tesina es el trabajo de Green On the analytic solution of the equation of fifth degree. Solucionando ecuaciones de grado a lo m as tres (que son solubles mediante una fórmula con radicales), encontrar las soluciones de cualquier ecuación de grado cinco equivale a encontrar las soluciones de una ecuación de la forma z5 + az + b = 0; esta familia de ecuaciones es conocida con el nombre de ecuaciones de Bring-Jerrard. Dado este hecho, es entonces deseable estudiar las soluciones de las ecuaciones de Bring-Jerrard. En esta tesina, vemos que la curva de soluciones compleja tiene una estructura natural de superficie de Riemann de género 4. Es un hecho notable que la curva de soluciones resulte ser uno de los poliedros estrellados de Kepler-Poison (el gran dodecaedro). Usando la estructura de superficie de Riemann de la curva de soluciones, podemos notar que solucionar una ecuación de grado 5 equivale a encontrar una uniformización para la curva compleja de género 4. El teorema de Uniformización garantiza la existencia de dicha función, pero el teorema no dice cómo obtenerla. La historia es diferente para las ecuaciones de grado 3 y 4, ya que en estos casos, la curva compleja de soluciones es simplemente la esfera de Riemann, por lo que no es necesario recurrir al teorema de Uniformización.
Instituto de Física y Matemáticas. Facultad de Ciencias Físico Matemáticas. Unidad Morelia del Instituto de Matemáticas de la UNAM. Programa Conjunto de Maestría en Matemáticas
Keywords: info:eu-repo/classification/cti/1; IFM-M-2016-0624; Tesina; Dodecaedro; Uniformización; Curva; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1229